2011
DOI: 10.1007/s00270-011-0172-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Anti-tumor Effects of Two Platinum Agents (Miriplatin and Fine-Powder Cisplatin)

Abstract: We confirmed the anti-tumor effect of ML and CL. There was no significant difference between the anti-tumor effect of ML and CL at 7 days postadministration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…In a multicenter phase II study that enrolled unresectable HCC cases [10], the response rate for cisplatin was 33.8%, whereas the response rates were 15%–20% for epirubicin [9] and mitomycin C [8]. Because miriplatin shows no cross-resistance with different generations of platinum agents [6, 22, 23], we examined double platinum treatments and anticipated additive effects of miriplatin and DDP-H, which currently provides the highest concentration of CDDP. The phase I study of this combination therapy showed no dose-limiting toxicity at a maximum dose of 120 mg/body for TOCE [24] and 65 mg/m 2 for HAIC.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter phase II study that enrolled unresectable HCC cases [10], the response rate for cisplatin was 33.8%, whereas the response rates were 15%–20% for epirubicin [9] and mitomycin C [8]. Because miriplatin shows no cross-resistance with different generations of platinum agents [6, 22, 23], we examined double platinum treatments and anticipated additive effects of miriplatin and DDP-H, which currently provides the highest concentration of CDDP. The phase I study of this combination therapy showed no dose-limiting toxicity at a maximum dose of 120 mg/body for TOCE [24] and 65 mg/m 2 for HAIC.…”
Section: Discussionmentioning
confidence: 99%
“…Although various chemotherapeutic agents have been used for treating HCC[16,17], platinum agents achieved a better response rate in a multicenter phase II study enrolling patients with unresectable HCC[29]. Based on these results and the fact that miriplatin showed no cross-resistance with different generations of platinum agents[30], we conducted a phase I study[18] and a phase II study[19] of combined therapy with miriplatin-TOCE and DDP-H-HAIC and demonstrated its safety and efficacy for patients with unresectable HCC. In fact, we could repeat the miriplatin-TOCE/DDP-H-HAIC combination therapy for the two cases in the present study without severe adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment in few HCC cases has shown cross-resistance with different generations of platinum agents [16,21,29]. In a rat model, miriplatin exhibited higher anti-tumour activity and lower hepatic toxicity than CDDP-lipiodol [16], and promising results have been reported in HCC patients [22-24].…”
Section: Discussionmentioning
confidence: 99%